Urgent Middle Cerebral Artery Embolectomy of Calcified Embolus After Intravenous Thrombolysis: 2-Dimensional Operative Video - Fiedler, Jiri; Ostry, Svatopluk; Bombic, Martin; Sterba, Ludek; Kostal, Petr (Operative neurosurgery (Hagerstown, Md.), 2019)
This video shows an urgent microsurgical embolectomy of the inferior division of the left middle cerebral artery in a patient treated by intravenous thrombolysis (IVT). Patient was eligible for endovascular mechanical thrombectomy1; however, the interventional radiologist was not comfortable performing the procedure given prior unsuccessful attempts to remove a calcified cerebral embolus.2 A 75-yr-old female presented with an acute ischemic stroke with isolated aphasia (NIHSS 9). Using the drip-and-ship concept, IVT (0.9 mg/kg rt-PA) was administered in a regional hospital. Fifty-five minutes after a complete recovery following IVT, multiple transient ischemic attacks of aphasia were observed. While the patient was a candidate for mechanical thrombectomy based on CT perfusion imaging, given the unsuccessful reports in the literature and the interventional radiologist's experience, the decision was made to offer microsurgical embolectomy of the calcified cerebral embolus.3 Informed consent for the procedure was obtained directly from the patient. Calcified, crumbly embolus was removed from a 5 mm longitudinal arteriotomy. The arteriotomy was sutured with interrupted 10-0 suture. Initial flow after the embolectomy was 6.5 mL/min. Upon inspection, a distal kink was found in the M2 and after repositioning, flow improved to 35 mL/min. Postoperative CT angiography documented complete recanalization. The clinical findings completely resolved (NIHSS 0) within 12 hr and remained unchanged at 3 mo and 1 yr. Informed consent was obtained from the patient for use of media for educational and publication purposes.
Keywords: Stroke; Perfusion imaging; Microsurgery; Brain ischemia; Tissue plasminogen activator; Middle cerebral artery; Thrombectomy; Embolectomy